"Pick and choose" opinion climate: How browsing of political messages shapes public opinion perceptions and attitudes. Issue 4 (2nd October 2019) - Sude, Daniel J.; Knobloch-Westerwick, Silvia; Robinson, Melissa J.; Westerwick, Axel
ABSTRACT: High-choice media environments allow people to cocoon themselves with like-minded messages (confirmation bias), which could shape both individual attitudes and perceived prevalence of opinions. This study builds on motivated cognition and spiral of silence theory to disentangle how browsing political messages (both selective exposure as viewing full articles and incidental exposure as encountering leads only) shapes perceived public opinion and subsequently attitudes. Participants ( N  = 115) browsed online articles on controversial topics; related attitudes and public opinion perceptions were captured before and after. Multi-level modeling demonstrated a confirmation bias. Both selective and incidental exposure affected attitudes per message stance, with stronger impacts for selective exposure. Opinion climate perceptions mediated selective exposure impacts on attitudes.